EFEK MODERASI LINGKUNGAN KELUARGA PADA PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI (Survei Pada Siswa Kelas XI IIS SMA Negeri Se-Kabupaten Bandung) - Neng Ersa Nurhasanah, - (2020)
This research is based on student learning outcomes in economic subject that have not reached the Minimum Completion Criteria (KKM) as indicated by the average result of the Final Semester Assessment (PAS) for the 2018/2019 school year of Public Senior High School in Bandung Regency. The purpose of this research was to determine the effect of independent learning on student learning outcomes in economic subjects with the family environment as a moderating variable. The research method is explanatory survey using a questionnaire as a data collection tool. The population in this research were 719 students from XI IIS Grade of Public Senior High School in Bandung Regency. By using a random sampling technique, a sample of 257 students was obtained. The data analysis technique used is hierarchical regression data analysis with Moderate Regression Analysis (MRA). The results showed: (i) The level of independent learning and the family environment was in the high category, while student learning outcomes showed that there were still many students who had not reached the Minimum Completion Criteria (KKM); (ii) The level of learning independence has a positive and significant effect on learning outcomes; (iii) the family environment does not moderate the effect of independent learning on learning outcomes because it is a predictor variable.